Factors Influencing The Occurrence Of Pulmonary Tuberculosis In The Productive Age Group - Tri Wahyuni; Rachmat Ramli; Rizky Rahadian Wicaksono; Abdul Rivai Saleh Dunggio; Arnianti Arnianti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Pulmonary tuberculosis (pulmonary TB) is an infectious disease that remains a public health problem, particularly among the productive age group. This age group has high levels of mobility and social activity, placing them at greater risk of TB transmission. The occurrence of pulmonary TB is influenced by various factors, both individual and environmental. This study aims to determine the factors influencing the occurrence of pulmonary tuberculosis in the productive age group. This study used quantitative methods with an analytical design and a case-by-case approach. control. The research sample consisted of a case group (pulmonary TB sufferers) and a control group (non-pulmonary TB sufferers) in health service area X. Data were collected using questionnaires and observation sheets, then analyzed using the Chi- Square test. The results showed that nutritional status, residential density, smoking habits, and home ventilation had a significant effect on the occurrence of pulmonary TB (p < 0.05).